Serum testosterone partially mediates the adverse effects of organophosphate pesticides exposure on growth indicators of children and adolescents - Zhenao Zhang; Xiaoya Sun; Jingyi Ren; Yadong Zhang; Rui Wen; Huanting Pei; Siqi Zhu; Bowen Yin; Ziyi Wang; Yuxia Ma (Ecotoxicology and Environmental Safety)
Environmental pollutants affect children’s and adolescents’ growth. However, the effect of organophosphate pesticides (OPPs) exposure on this population remains unclear. This study applied a comprehensive statistical framework to evaluate the effects of multiple OPP metabolites on growth indicators in individuals aged 6–19 using data from the National Health and Nutrition Examination Survey (NHANES). The framework integrated latent class analysis (LCA), survey-weighted generalized linear regression models (SWGLMs), weighted quantile sum (WQS) regression, and bayesian kernel machine regression (BKMR). The role of total testosterone (TT) as a mediator was assessed. Network pharmacology methods were used to identify key targets and therapeutic drugs. LCA identified three exposure patterns for OPP metabolites: High DMP-High DEP (N = 145), Low DMP-Low DEP (N = 689), and High DMP-Low DEP (N = 97). SWGLMs, WQS, and BKMR demonstrated a negative association between OPPs exposure and growth indicators, particularly in females and adolescents. TT mediated this association, with mediation proportions ranging from 8.7 % to 35.7 %. Network pharmacology analysis identified 120 key targets, and pterostilbene emerged as a potential therapeutic agent. These findings suggest that OPPs exposure adversely affects children’s and adolescents’ growth, partly mediated by TT. Adolescents and females may be particularly vulnerable. Pterostilbene supplementation represents a potential strategy to mitigate these adverse effects.